Merdeka Belajar dalam Pembelajaran Bahasa Arab untuk Pustakawan di UIN Sunan Kalijaga Yogyakarta - Aprilia; R.M.S Gufroni (Yayasan Hurriah, Banda Aceh, 2021)
Abstract This research is a type of field research using qualitative approach. This study aims to determine the implementation of freedom to learn and the problems faced in Arabic courses for librarians. Data were collected through observation, interviews, and questionnaires. The object of this research is 4th-semester students, Library Science Study Program. The results of this study indicate that in freedom to learn, students play an active role as learning centers, students are given the freedom to explore the material independently, widely, and not limited to the material presented by the lecturer in the classroom, then students are assigned to present the knowledge they have learned. The supporting lecturer acts as a facilitator, meaning as a provider of directions for the outline of learning materials. The obstacles faced are: (1) Students find it difficult to find reference sources independently. (2) For students who have not mastered the basics of Arabic, are having difficulty understanding the learning material. (3) Students are required to give more effort to understand and present learning materials optimally. Keywords: Freedom to learn, Arabic, Librarian. Abstrak Penelitian ini merupakan jenis penelitian lapangan dengan menggunakan pendekatan kualitatif. Penelitian ini bertujuan untuk mengetahui pelaksanaan merdeka belajar dan problematika yang dihadapi dalam mata kuliah bahasa Arab untuk pustakawan. Pengumpulan data dilakukan melalui observasi, wawancara, dan angket. Objek penelitian ini adalah mahasiswa semester 4, Program Studi Ilmu Perpustakaan. Hasil penelitian ini menunjukkan bahwa dalam pembelajaran merdeka, mahasiswa berperan aktif sebagai pusat pembelajaran, mahasiswa diberi kebebasan untuk mengeksplor materi secara mandiri, luas, dan tidak terbatas atas materi yang disampaikan oleh dosen di dalam kelas, kemudian mahasiswa ditugaskan untuk mempresentasikan pengetahuan yang telah dipelajarinya. Dosen pengampu berperan sebagai fasilitator, artinya sebagai pemberi arahan garis besar materi pembelajaran. Adapun hambatan-hambatan yang dihadapi ialah: (1) Mahasiswa merasa kesulitan dalam mencari sumber referensi secara mandiri. (2) Bagi mahasiswa yang belum menguasai dasar-dasar bahasa Arab, mereka kesulitan dalam memahami materi pembelajaran. (3) Mahasiswa dituntut untuk memberikan effort lebih agar dapat memahami dan mempresentasikan materi pembelajaran secara maksimal. Kata Kunci: Pembelajaran Merdeka, Bahasa Arab, Pustakawan.